Power Minimization Using Rate Splitting With Statistical CSI in Cloud-Radio Access Networks - Alameer Ahmad, Alaa; Dahrouj, Hayssam; Chaaban, Anas; Al-Naffouri, Tareq Y.; Sezgin, Aydin; Shamma, Jeff. S.; Alouini, Mohamed-Slim (Frontiers in Communications and Networks, 2021)
Minimizing the power consumption in mobile communication networks while ensuring a minimum quality of service (QoS) for applications is essential in light of the unprecedented expected increase in the number of connected devices and the associated data traffic in beyond the fifth generation of wireless networks (B5G). The paper considers a cloud-radio access network (C-RAN) model where a central processor (CP) is connected to the base stations (BSs) via limited capacity fronthaul links. In the context of our C-RAN setting, we consider the practical case where the CP has only statistical knowledge of channel state information (CSI). While conventional wireless systems adopt treating interference as noise (TIN) strategy to deal with the interference in the network, this paper instead considers that the CP applies rate splitting (RS) strategy by dividing each user’s message into two parts: a private part to be decoded by the intended user only and a common part to be decoded by a subset of the users, for the sole reason of interference mitigation in the network. To best account for the channel estimation errors, the paper addresses the problem of transmit power minimization under minimum QoS constraints on the achievable ergodic rate per-user, so as to determine the beamforming vectors of the private and common messages as well as the rate allocated for all the users. The considered problem is of stochastic, complex, and non-convex nature. This paper addresses the problem intricacies through an iterative approach that leverages both the sample average approximation (SAA) technique and the weighted-minimum mean squares error (WMMSE) algorithm to obtain a stationary point of the optimization problem at the asymptotic regime. The numerical results demonstrate the gain achieved with RS strategy as compared to TIN, especially under high QoS requirements.